The Strategic Role of Millennial Women in Advancing MSMEs in the Digital Economy Era - Nurhayani Nurhayani; Jumardi Jumardi; Hasisa Haruna (Indonesian Journal of Business and Entrepreneurship Research, 2025)
The development of the MSME sector which is supported by the digital economy, creates many new innovations. The transformation towards a digital-based economy is mostly driven by millennial women. This study aims to analyze the strategic role of millennial generation women in the digital economy era. The research method used is the descriptive qualitative method. The data collection method used is the method of observation, interviews, and documentation. Data were analyzed through three paths, namely data reduction, data presentation, and drawing conclusions. The results of the study show that respondents play an important role in economic development through MSMEs. The results of this study prove: 1) millennial women have an important and strategic role in starting businesses, creating new products, managing business finances, and marketing their business products using digital media; 2) on average business actors understand their position as women, respondents say that there are no norms/rules that prohibit women from working, and MSMEs managed by respondents have received permission and support from husbands or family; 3) MSME actors have benefited from the digital economy, especially in the marketing process, the benefits derived from social media activities greatly support the development of their businesses, and the government is very supportive of the efforts made by women entrepreneurs in helping improve the regional and national economy.